The effects of melatonin on prostate tissue of orchiectomized - Semerciöz, Atilla; Şenol, F. Ahmet; Onur, Rahmi; Orhan, Irfan; Yüzgeç, Veysel (My University, 2003)
Introduction: Melatonin effective in many organs is a hormone secreted from the pineal gland. When human prostate hyperplasic etiology is considered, additional to an androgen - estrogen imbalance state, both melatonin and miscellaneous etiologic factors may play a role in the mentioned condition. Especially it is well known that human prostate tissues contains specific connecting zones and this condition is related with localized microsonial fractions at the glandular epithelium of a benign prostate tissue. Such relationship draws attention that various mechanisms may play an active role in the etiopathogenesis of a benign prostate hyperplasia (BPII). To investigate the effect of melatonin on prostate, levels of prostate melatonin, 6-hydroxymelatonine and serotonin and weights of the prostate and vesicula seminalis were evaluated in orchiectomized rats. Materials and Methods: The sensitivity of prostate to melatonin was assessed in a total of bilaterally orchiectomized 40 Wister-Albino type rats that were randomized in four groups and were waited for seven days to allow alterations to occur in the weight in the prostate gland. Group 1: Control group, only orchiectomized rats. Group 2: Orchiectomized rats: Group of rats where melatonin was applied for a period of 4 days/5 mg/kg to the musculus bicepsfemoris semitendineus and to the musculus gluteus maximus muscles of the right rear legs after a period of 7 waiting days. Group 3: Orchiectomized rats: group of rats where testosterone propionate was applied for 4 days/1 mg/kg subcutaneously to the abdominal skin after 7 waiting days. Group 4: Orchiectomized rats: group of rats where melatonin and testosterone propionate was applied for 4 days/5 mg/kg to the musculus bicepsfemoris semitendineus and the musculus gluteus maximus muscles of the right rear legs for 4 days/1 mg/kg subcutaneously to the abdominal skin after 7 waiting days. To investigate the effect of melatonin on the prostate, prostate melatonin, 6-hydoxymelatonin, serotonin levels and the weights of the prostate vesicula seminalis were assessed in orchiectomized rats. Result: In group 2 where rats were treated only with melatonin, the weight of prostate and vesicula seminalis were found significantly lower when compared with rats in group 3 as these rats were treated only with testosterone. Melatonin was not found in the prostate in none of the groups, but the level of 6-hydroxymelatonin was determined significantly higher in group 2 when compared to group 3. Serotonin level values in group 4 were significantly higher according to group 2. Conclusion: The possible effect of melatonin on the prostate is commonly to avoid the growth of the prostate by the means of an active metabolite, 6-hydroxymelatonin. Non-invasive and new medical therapy alternatives are still under investigation and as a medical alternative melatonin as a new hormone in BPII and requires further studies.
Orşiektomize Ratlarda Melatonxinin Prostat Dokusuna Etk?ileri
Keywords: 6-hidroksimelatonin; Melatonin; Prostate